Circumscribed Morphea and Breast Asymmetry in an Adolescent. (23rd December 2013) - Massa, António Augusto Fernandes; Baptista, Armando Manuel Simões; Couceiro, António Manuel Ferreira da Silva Abreu; Ferreira, Eduarda Macedo Osório Morais
Abstract : Morphea is a rare fibrosing disorder of the skin and underlying tissues. Circumscribed morphea presents with less than three discrete indurated plaques and breasts are commonly affected in women. We report the case of a 12-year-old female with a right infra-areolar, nontender, brownish patch and asymmetry of the right breast with 2 years of evolution. Skin biopsy showing thickening of the dermal collagen bundles confirmed the clinical diagnosis of morphea. After a 3-year follow-up period without progression of disease, reconstructive surgery is scheduled. Plaque morphea can involve all layers of the skin but associated breast deformity is rare. It can mimic benign and malignant breast disorders justifying the benefit for early tissue biopsy. Breast morphea generally has a good prognosis but hyperpigmentation and breast deformity in young girls have been rarely described. An early diagnosis can possibly lead to a therapeutic intervention with a different outcome, as it can be the source of severe psychological and social issues in a delicate period of development such as adolescence.